Role of Nrf2 Signaling Cascade in Breast Cancer: Strategies and Treatment - Kumar, Hitesh; Kumar, Rachna M.; Bhattacharjee, Devanjali; Somanna, Preethi; Jain, Vikas (Frontiers in Pharmacology, 2022)
Breast cancer is the second leading cancer among all types of cancers. It accounts for 12% of the total cases of cancers. The complex and heterogeneous nature of breast cancer makes it difficult to treat in advanced stages. The expression of various enzymes and proteins is regulated by several molecular pathways. Oxidative stress plays a vital role in cellular events that are generally regulated by nuclear factor erythroid 2-related factor 2 (Nrf2). The exact mechanism of Nrf2 behind cytoprotective and antioxidative properties is still under investigation. In healthy cells, Nrf2 expression is lower, which maintains antioxidative stress; however, cancerous cells overexpress Nrf2, which is associated with various phenomena, such as the development of drug resistance, angiogenesis, development of cancer stem cells and metastasis. Aberrant Nrf2 expression diminishes the toxicity and potency of therapeutic anticancer drugs and provides cytoprotection to cancerous cells. In this article, we have discussed the attributes associated with Nrf2 in the development of drug resistance, angiogenesis, cancer stem cell generation and metastasis in the specific context of breast cancer. We also discussed the therapeutic strategies employed against breast cancer exploiting Nrf2 signaling cascades.